Handbook of Political Violence and Children 2020
DOI: 10.1093/oso/9780190874551.003.0017
|View full text |Cite
|
Sign up to set email alerts
|

Children, Not Soldiers

Abstract: Recruiting children under the age of 15 years and using them to actively participate in hostilities is forbidden under international law and amounts to an international crime. Nonetheless, parties continue to enlist and conscript children, putting their lives in danger by exploiting them, very often not only for military purposes. After outlining the legal foundations of the prohibition on recruiting and using children, this chapter aims at providing an overview of the tools and strategies, including the UN ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Furthermore, the link between poverty and crime was found to consistently pertain to youth’s involvement in violence in general (Fougère et al, 2009; Mazorodze, 2020; McAra & McVie, 2016), and in political violence in particular (Musa, 2016; Barakat & Urdal, 2009). Moreover, social and cultural attitudes can also contribute to the mobilization of young adults in violent conflicts (Capone, 2020; Yarrow, 2020), whereas an absence of infrastructure for their welfare and well-being, coupled with a lack of employment opportunities may also motivate youth to engage in terrorism (Ray, 2020).…”
Section: Youth Terrorist Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the link between poverty and crime was found to consistently pertain to youth’s involvement in violence in general (Fougère et al, 2009; Mazorodze, 2020; McAra & McVie, 2016), and in political violence in particular (Musa, 2016; Barakat & Urdal, 2009). Moreover, social and cultural attitudes can also contribute to the mobilization of young adults in violent conflicts (Capone, 2020; Yarrow, 2020), whereas an absence of infrastructure for their welfare and well-being, coupled with a lack of employment opportunities may also motivate youth to engage in terrorism (Ray, 2020).…”
Section: Youth Terrorist Activitymentioning
confidence: 99%
“…Scholars have underscored the importance of intervention programs capable of contributing to lowering adolescents’ involvement in political violence. However, such programs’ success is contingent on the timing of the intervention process, as well as the implementation of legal and political aspects necessary for these programs (Capone, 2020; Greenbaum et al, 2020; Yarrow, 2020).…”
Section: Youth Terrorist Activitymentioning
confidence: 99%
“…Empirical research on Jihadist terrorism in Europe examining cases between 2001 and 2006 noted that the average age of arrest was 27.3 years (Bakker, 2006), while other research noted that lone actor terrorists tend to be males in their mid-30s (Gill et al , 2014; Perry et al , 2018). However, the age at which offenders commit their first crime, are first arrested, become radicalised or become involved in extremism may change over time due to sociocultural attitudes and a variety of contextual factors (Capone, 2020). For example, it is suggested that the number of radicalised “youths” involved in terrorism has increased notably over the past decade (Sela-Shayovitz et al , 2023).…”
Section: Introductionmentioning
confidence: 99%